International migration, foreign direct investment, and development stage in developing economies. Issue 2 (11th December 2018) - Phyo, Ei Ei; Goto, Hideaki; Kakinaka, Makoto
Abstract: The existing empirical results on the relationship between FDI and migration are rather mixed. This study reevaluates, both theoretically and empirically, how inward FDI relates to emigration in developing countries. Our model illustrates that the relationship between inward FDI and emigration flows depends on the development stage of a developing country, that is, there is a positive association between inward FDI and emigration flows for relatively less‐developed countries but a negative association between these two variables for relatively developed countries. We confirm the empirical validity of our model prediction using the panel data of 21 OECD and 51 non‐OECD countries during the period from 2003 to 2012. Our results argue that as economic development proceeds in a developing country, the home effect of inward FDI associated with intensified labor demand would dominate the linkage effect that induces the brain drain problem through enhancing the socioeconomic ties with migrant networks.